Development Strategies of the Textile Industry of Uzbekistan - Olimov Anvarzhon Atamirzaevich; Abdukarimova Muslima Abduaziz Qizi (Zien Journals, 2022)
The article assesses the results of the activities of the textile and clothing and knitwear industry of Uzbekistan for 2017-2020. The role of the industry in the development of the economy and industry, the growth of exports, the introduction of a cluster development model, and the provision of employment are shown. Development priorities are shown.
Keywords: assesses; Development; textile; clothing